A mouse model of retinal hypoperfusion injury induced by unilateral common carotid artery occlusion. (December 2020) - Lee, Deokho; Kang, Heekyoung; Yoon, Ki Young; Chang, Yuan Yi; Song, Hyun Beom
Abstract: Retina, one of the highest oxygen demanding tissues, is vulnerable to vascular insufficiencies, and various ocular vascular disorders can cause chronic retinal ischemia. To investigate the pathophysiology, rodent models developed by bilateral common carotid artery occlusion (BCCAO) have been utilized. However, mice lack posterior communicating arteries in the circle of Willis and cannot endure the brain ischemia induced by the bilateral occlusion. A mouse model to better reflect the localized ischemic stress in the retina without affecting the brain is still needed. Here, we established a mouse model of ischemic injury by permanent unilateral common carotid artery occlusion (UCCAO). Adult male mice were subjected to UCCAO, and changes in the ipsilateral retina were examined in comparison with the contralateral retina. Delayed perfusion was observed in the ipsilateral retina right after the occlusion and was not recovered later on. Common features of retinal ischemia were observed: hypoxia-inducible factor (HIF) stabilization; upregulation of hypoxia-responsive genes; altered levels of cytokines and chemokines. Activation of astrocytes and Müller cells in the inner retina was detected at day 2, and thinning of the inner retinal layer became significant at week 10. Together, our model can simulate retinal ischemia with morphological and molecular changes. It can be utilized to investigate pathophysiology of ischemic retinopathies. Highlights: A mouse model for retinal hypoperfusion injury was established. Unilateral common carotid artery occlusion induces ischemia in the ipsilateral retina. Delayed perfusion and upregulation of Epo were persistent 4 weeks after the occlusion. Inner retinal thinning became remarkable 10 weeks after the occlusion.